Internet’s Dirty Secret: Assessing the Impact of Online Intermediaries on HIV Transmission1 - Chan, Jason; Ghose, Anindya (MIS Quarterly, 2014)
Online platforms offer access to a larger social group than is generally available through offline contacts, making the Internet an emerging venue for seeking casual sex partners. The ease of seeking sex partners through classified ad sites may promote risky behaviors that increase the transmission of STDs. In this paper, using a natural experiment setup, we investigate whether the entry of a major online personals ad site, Craigslist, increases the prevalence of HIV over a 10 year period from 1999 to 2008 across 33 states in the United States. After controlling for extraneous factors, our results suggest that the entry of Craigslist is related to a 15.9 percent increase in HIV cases. Our analysis suggests that the site entry produces an average of 6,130 to 6,455 cases of HIV infection in the United States each year, mapping out to between $62 million and $65.3 million in annual treatment costs. In addition, the analyses reveal that nonmarket-related casual sex is the primary driver of the increase in HIV cases, in contrast to paid transactions solicited on the site (e.g., escort services and prostitution), which has a negative relationship with HIV trends. These findings are essential to understanding the social routes through which HIV transmission takes place and the extent to which site entry can influence HIV trends. Implications for healthcare practitioners and policy makers are discussed.